Optimizing Cash Waqf Through Improved Literacy Based Kantor Urusan Agama (KUA) in Indonesia - Hakim, Muhammad Hanif (EJESH: Journal of Islamic Economics and Social, 2025)
This study analyzes the role of the Office of Religious Affairs (KUA) in promoting cash waqf literacy in Indonesia. Using a qualitative approach, it identifies key constraints such as limited public awareness, weak coordination, and regulatory gaps. Findings show that KUA plays a strategic role in socializing cash waqf, yet its efforts are often hampered by limited resources and lack of structured programs. The study proposes integrated strategies involving education, digital tools, and inter-agency collaboration to enhance KUA’s effectiveness in optimizing cash waqf for socio-economic development